2020
DOI: 10.1515/ijamh-2019-0264
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of attachment relationships, psychological problems and negative automatic thoughts among college students in Pakistan

Abstract: AbstractObjectivesThe present pilot study examined the associations between attachment relationships, psychological problems, and negative automatic thoughts among late adolescents in Rawalpindi, Pakistan.SubjectsA total of 98 participants (male = 49, female = 49) were recruited from government colleges in Rawalpindi, Pakistan.Methods Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Our mediation model of automatic thoughts was also consistent with previous studies indicating that automatic thoughts are an important proximal factor, through which an undesirable family environment was linked to physical and mental development (Kazdin, 1990;Hou et al, 2020). Individuals from families with more parental conflicts and undesirable parent-child relationships were more likely to develop characteristics such as low self-evaluation and low self-esteem, which were reflected through individuals' negative automatic thoughts (Irfan and Zulkefly, 2020). These negative cognitive styles would enhance individuals' negative internal working model, it may motivate individuals to employ negative coping skills such as escaping from reality and indulging in virtual mobile phones when they make excessive inferences about negative stimuli (Hjemdal et al, 2013;Irfan and Zulkefly, 2021).…”
Section: Discussionsupporting
confidence: 89%
“…Our mediation model of automatic thoughts was also consistent with previous studies indicating that automatic thoughts are an important proximal factor, through which an undesirable family environment was linked to physical and mental development (Kazdin, 1990;Hou et al, 2020). Individuals from families with more parental conflicts and undesirable parent-child relationships were more likely to develop characteristics such as low self-evaluation and low self-esteem, which were reflected through individuals' negative automatic thoughts (Irfan and Zulkefly, 2020). These negative cognitive styles would enhance individuals' negative internal working model, it may motivate individuals to employ negative coping skills such as escaping from reality and indulging in virtual mobile phones when they make excessive inferences about negative stimuli (Hjemdal et al, 2013;Irfan and Zulkefly, 2021).…”
Section: Discussionsupporting
confidence: 89%
“…Laible, Carlo, & Roesch (2004) concluded that parental attachment had direct impacts on both male and female college students' self-esteem, whereas peer attachment had indirect impacts on the female students' self-esteem. Irfan & Zulkefly (2020) wrote that among Pakistani college students, maternal and peer attachment had significant negative correlations with depression, anxiety, and automatic thought. Delvecchio et al (2020) reported significant correlations between paternal/maternal attachment levels and self-esteem among Polish adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…Automatic thoughts are considered to be automatic because they may be initiated by both conscious and unconscious thoughts, and the subsequent cognitive processes do not require a conscious effort (Buschmann et al, 2018). A study conducted on students has shown that depressive symptoms worsen and anxiety increases as the automatic thoughts increase (Alsaleh et al, 2016; Irfan & Zulkefly, 2020; Yapan et al, 2020). Nurses are the professionals who are expected to have functional thinking and effective communication and coping strategies, and not to have distorted beliefs which are frequently present in interpersonal relationship.…”
Section: Introductionmentioning
confidence: 99%
“…Automatic thoughts are considered to be automatic because they may be initiated by both conscious and unconscious thoughts, and the subsequent cognitive processes do not require a conscious effort (Buschmann et al, 2018). A study conducted on students has shown that depressive symptoms worsen and anxiety increases as the automatic thoughts increase (Alsaleh et al, 2016;Irfan & Zulkefly, 2020;Yapan et al, 2020).…”
mentioning
confidence: 99%